Expectations, satisfaction and loyalty in health and fitness clubs. (23rd February 2009) - Pedragosa, Vera; Correia, Abel
The study of satisfaction has been the focus of much research in the area of marketing, in particular, on the nature of the relationships fostered by satisfaction between the service and the consumer. In the present study, global satisfaction, measured in the long term, is evaluated with respect to three constructs: expectations, facilities and loyalty. Expectations are considered as an innovative construct in their relationship with the consumer satisfaction in the Health and Fitness Clubs (HFC). Facilities are measured in the short term in order to evaluate the satisfaction by attributes, that is, all of the aspects encountered in using the various services provided by the HFCs. Loyalty is analysed by means of repeat purchases, recommendations to third parties and the frequency of use. The sample from a questionnaire comprises 463 respondents who are clients of two HFCs in the Greater Lisbon suburb of Oeiras, Portugal. The results suggest that satisfaction is an intermediate variable that is positively related to various other constructs and of crucial importance in determining the loyalty in HFCs.